1993
DOI: 10.1093/oxfordjournals.aje.a116617
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution and Daily Mortality in Birmingham, Alabama

Abstract: Several recent studies have reported associations between common levels of particulate air pollution and small increases in daily mortality. This study examined whether a similar association could be found in the southern United States, with different weather patterns than the previous studies, and examined the sensitivity of the results to different methods of analysis and covariate control. Data were available in Birmingham, Alabama, from August 1985 through 1988. Regression analyses controlled for weather, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
147
2
5

Year Published

1994
1994
2008
2008

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 296 publications
(161 citation statements)
references
References 0 publications
7
147
2
5
Order By: Relevance
“…This association has been reported for Detroit (Schwartz 1991), St. Louis and Easter Tennessee , Utah Valley (Pope et al 1992), Minneapolis (Schwartz 1992), and Birmingham, Alabama (Schwartz 1993). While there will continue to be some uncertainty about the precise magnitude of the effect, these studies tend to support the quantitative estimates of the studies reported above.…”
Section: More Recent Daily Time-series Studiessupporting
confidence: 53%
“…This association has been reported for Detroit (Schwartz 1991), St. Louis and Easter Tennessee , Utah Valley (Pope et al 1992), Minneapolis (Schwartz 1992), and Birmingham, Alabama (Schwartz 1993). While there will continue to be some uncertainty about the precise magnitude of the effect, these studies tend to support the quantitative estimates of the studies reported above.…”
Section: More Recent Daily Time-series Studiessupporting
confidence: 53%
“…[1][2][3] These studies also indicate higher relative risk estimates for the elderly and for those with pre-existing respiratory or cardiovascular diseases. 1,[4][5][6] There is limited information about the contributions of particles of outdoor origin to actual human exposures of such at-risk groups to support the plausibility of these epidemiological findings.…”
Section: Introductionmentioning
confidence: 82%
“…We used a generalized additive model (GAM) (11) to regress daily stroke death counts for each pollutant, while controlling for seasonal and longterm trends, day of the week and meteorologic influences (temperature, relative humidity, and barometric pressure) (12). Because there was a systematic difference in daily mortality among weekdays, we included terms for days of the week in the models.…”
Section: Methodsmentioning
confidence: 99%